Optimizing Islamic Education Towards the Golden Era of Indonesia - Muhammad Annas Budiarto; Unik Hanifah Salsabila (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
Optimizing Islamic education plays an important role in preparing Indonesian citizens to excel in quality in terms of education in welcoming Indonesia's golden era. Optimizing education leads to maximizing human resources, especially for school students. They are the main encouragement during the golden era because they are entering a productive period. This article aims to provide an understanding of how important educational factors are in preparing for the golden age of Indonesia by analyzing the urgency and designing the steps to be used. This study uses the library research method, using pragmatic content analysis, thematic content analysis, analysis of sign means, continued by processing it into new data where the results of this study are the exposure of optimizing education to reach the golden era of Indonesia from reviewing and analyzing and integrating various related reference sources.